Teresa speaks to us of God: the art of telling an experience - Guerrero Pérez, Irene (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The experience of God implies the call to be shared. In Teresa de Jesús we can see that such communication, as a guarantee of its authenticity, requires a gradual process of understanding in which the grace makes its way through writing, speech given and lived. There are also attitudes and conditions that cannot be missed when speaking of God, such as naturalness, faithfulness, parrhesia and narrative force.
Keywords: spiritual communication; mysticism; authenticity; favor; witness